2014
DOI: 10.1002/cncy.21453
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic features of parathyroid fine‐needle aspiration on ThinPrep preparations

Abstract: BACKGROUND: Previous studies have provided cytologic criteria that aid in the recognition of parathyroid tissue on aspirate smears, including high cellularity, the presence of naked nuclei, loose 2-dimensional clusters, and papillary architecture. However, to the authors knowledge, the cytomorphologic features of parathyroid fine-needle aspiration (FNA) on liquid-based preparations have not been previously described. METHODS: The authors retrospectively reviewed all parathyroid FNAs that had aspirate smears an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
1
16
2
Order By: Relevance
“…Some studies suggest subtle differences between parathyroid carcinoma and benign lesions; however, most studies found that in most occasions this distinction is not possible. 9 Tseleni-Balafouta et al 11,12 noted that intranuclear cytoplasmic inclusions were present only in carcinomas; on the contrary, other investigators 11,12 reported intranuclear inclusions in parathyroid adenomas. In rare cases, however, there may be marked pleomorphism with bizarre giant cells, necrosis, and abnormal mitoses, in which cases a diagnosis of carcinoma can be suggested.…”
Section: Cytomorphologic Features Of Parathyroid Lesionsmentioning
confidence: 94%
See 4 more Smart Citations
“…Some studies suggest subtle differences between parathyroid carcinoma and benign lesions; however, most studies found that in most occasions this distinction is not possible. 9 Tseleni-Balafouta et al 11,12 noted that intranuclear cytoplasmic inclusions were present only in carcinomas; on the contrary, other investigators 11,12 reported intranuclear inclusions in parathyroid adenomas. In rare cases, however, there may be marked pleomorphism with bizarre giant cells, necrosis, and abnormal mitoses, in which cases a diagnosis of carcinoma can be suggested.…”
Section: Cytomorphologic Features Of Parathyroid Lesionsmentioning
confidence: 94%
“…Thyroid epithelial cells have also been reported to be present in up to 31% of parathyroid aspirates, and extra caution must be exercised not to confuse these contaminant cells with the lesional cells. 4,7,9 Parathyroid cells, particularly the oncocytic variant of parathyroid adenoma, can have abundant cytoplasm that can easily be confused with Hürthle cell lesions of the thyroid (Figs. 1D, E).…”
Section: Differential Diagnosismentioning
confidence: 98%
See 3 more Smart Citations